Segmental phonological properties in Thakali: a typological perspective - Regmi, Dan Raj; Regmi, Ambika (Gipan, 2019)
Thakali, a Tibeto-Burman language spoken in Nepal, exhibits some typologically interesting properties in the domain of segmental phonology. It presents a rich inventory of 33 segmental consonant phonemes and a set of six monophthongal vowels with murmured voice (i.e., breathy) counterparts. The syllable structure at the maximum consists of (C) (X) V (C), where X stands for a glide or liquid phoneme. Thakali as a Bodish language contains retroflex series as well as distinct alveolar fricatives and affricates and lacks phonemic voicing contrasts. As a member of the Gurungic cluster of West Bodish sub-section, Thakali shares such properties with other West- Bodish languages, viz., Chantyal, Manange, Gurung, Magar Kaike, Ghale, Seke, Nar-Phu, Western Tamang and Eastern Tamang. Unlike a Bodish language, Thakali lacks phonemically nasalized vowels. Thakali, like Chantyal, presents contrasts involving voice onset time and murmur. Such contrasts are attested in stops, affricates, fricatives, trills/taps and laterals in Thakali. However, unlike Chantyal, Thakali contains murmured trill/tap and murmured lateral with voiceless onset like Seke and Nar-Phu. Such properties are exclusively absent in other West Bodish languages. While uplifting Thakali, a shifting language, from sustainable identity to sustainable orality, such properties typical in South Asia (Noonan, 2003a: 316) have to be fully maintained.